Analisis Kepuasan Pengguna Layanan Pembukaan Rekening Online Pada BNI KM9 Palembang - Fattarsyah, Sultan Daffa; Ruliansyah, Ruliansyah (MDP Student Conference, 2024)
Customer satisfaction is a crucial indicator for a bank to assess the performance and quality of its banking system services. User satisfaction is influenced by various factors, such as service quality, information quality, system quality, and the features offered. This study aims to analyze user satisfaction levels in online account opening at Bank Negara Indonesia KM9 Musi Palembang Branch, using the Kano Model. The research methodology applies the Kano Model with sample data search using the Slovin formula. Data collection is carried out by observation, questionnaire, and interview methods. The research results show that users are generally satisfied with the speed of service and clarity of information as key factors. However, security levels and process ease require improvement.